Formulation And Evaluation Of Some Framycetin Sulphate Ointment - NIMBEKAR T.P.; BHANGE P.G.; WANJARI B.E.; MEHERE A.P. (International Journal of Pharma and Bio Sciences, 2012)
In present work attempt was made to formulate the topical preparation containing amino glycoside antibiotic framycetin sulphate, a wide spectrum antibiotic against gram positive as well as gram negative bacteria. The topical or dermatological preparations when applied to the skin for their physical effects i.e. for their ability to act as skin protectants, lubricant, emollient, drying agents, etc. Another group of topical preparations contain rubifacients, counterirritants, astringent, keratolytics agent, altering pigmentation, sclerosis agents, etc. Ointments are the semisolid preparation intended for external application. The four formulations of 1% w/w framycetin sulphate were developed using soft paraffin, stearic acid, white bees wax and PEG 4000. Different formulations i.e. F1, F2, F3, F4 and marketed preparation were evaluated by the parameters, where framycetin ointment F2 was lower release rate as compared to marketed formulation of Soframycein and formulation F4 shows higher release rate with the marketed ointment. In-vitro antimicrobial activity was determined by measuring the zone of inhibition’s of formulations by using various microorganisms